Design, synthesis, and bioactivity evaluation of novel Bcl-2/HDAC dual-target inhibitors for the treatment of multiple myeloma. Issue 3 (1st February 2019) - Zhou, Ruolan; Fang, Shaoyu; Zhang, Minmin; Zhang, Qingsen; Hu, Jian; Wang, Mingping; Wang, Chongqing; Zhu, Ju; Shen, Aijun; Chen, Xin; Zheng, Canhui
Graphical abstracts: Highlights: A series of Bcl-2/HDAC dual-target inhibitors were designed and synthesized. Compounds 7e –7g showed good inhibitory activities against HDAC6 and Bcl-2 protein. Compounds 7e –7g displayed good inhibitory activities against RPMI-8226 cell line. Abstract: Multiple myeloma (MM) is the second most common haematological malignancy. Almost all patients with MM eventually relapse, and most recommended treatment protocols for the patients with relapsed refractory MM comprise a combination of drugs with different mechanisms of action. Therefore novel drugs are in urgent need in clinic. Bcl-2 inhibitors and HDAC inhibitors were proved their anti-MM effect in clinic or under clinical trials, and they were further discovered to have synergistic interactions. In this study, a series of Bcl-2/HDAC dual-target inhibitors were designed and synthesized. Among them, compounds 7e –7g showed good inhibitory activities against HDAC6 and high binding affinities to Bcl-2 protein simultaneously. They also displayed good growth inhibitory activities against human MM cell line RPMI-8226, which proved their potential value for the treatment of multiple myeloma.